Kepatuhan, Pemeriksaan, dan Penghindaran Pajak sebagai Determinan Penerimaan Pajak - Ulfa Rabiyah; Dewi Anggraeni; Nur Fatwa Basar (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2026)
This study aims to analyze the influence of taxpayer compliance, tax audits, and tax avoidance on tax revenue. The research method used is a quantitative approach with multiple linear regression analysis, using data obtained from individual taxpayers at relevant agencies. Data analysis used descriptive statistics and path model regression with IBM SPSS 25. The results show that taxpayer compliance and tax audits have a positive and significant effect on tax revenue, while tax avoidance has a negative but insignificant effect. These findings confirm that increasing tax compliance and the effectiveness of tax audits are key factors in optimizing tax revenue.